Developing Two Rapid Protein Extraction Methods Using Focused-Ultrasonication and Zirconia-Silica Beads for Filamentous Fungi Identification by MALDI-TOF MS - Ning, Ya-Ting; Yang, Wen-Hang; Zhang, Wei; Xiao, Meng; Wang, Yao; Zhang, Jing-Jia; Zhang, Ge; Duan, Si-Meng; Dong, Ai-Ying; Guo, Da-Wen; Zou, Gui-Ling; Wen, Hai-Nan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Filamentous fungi identification by Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been challenging due to the lack of simple and rapid protein extraction methods and insufficient species coverage in the database. In this study, we created two rapid protein extraction methods for filamentous fungi: an one-step zirconia-silica beads method (ZSB) and a focused-ultrasonication method (FUS). A total of 602 filamentous fungi isolates were included. Both methods were evaluated with the VITEK MS compared to the routine method. the more efficient method was applied to build a filamentous fungi in-house spectra library for the M-Discover 100 MS. The routine and FUS method were then performed in parallel to verify the accuracy and commonality of the in-house library. Using the two optimized methods, the dedicated operating time before MALDI-TOF MS analysis was reduced from 30 mins (routine method) to 7 (ZSB) or 5 (FUS) mins per sample, with only a few seconds added for each additional strain. And both ZSB and FUS methods identified isolates from most mold types equal to or better than the routine method, and the total correct identification rate using VITEK MS was 79.67%, 76.42% and 76.42%, respectively. After excluding the isolates that lacked reference spectra, the success rate of identification was 92.52% (99/107) vs 96.26% (103/107) vs 94.39% (94/107) respectively, and the accuracy was all up to 100% for Aspergillus, Penicillium, Scedosporium spp.. An in-house library of M-Discover MS was successfully built with 540 reference spectra from 135 isolates from 42 species belonging to 18 genera using the ZSB method. Analysis of 467 isolates resulted in 97.22% correctly identified isolates to the species level by the ZSB method versus 95.50% by the routine method. The two novel methods are time- and cost-effective and allow efficient identification of filamentous fungi while providing a simplified procedure to build an in-house library. Thus, more clinical laboratories may consider adopting MALDI-TOF for filamentous fungi identification in the future.